Transformative pathways towards good governance in high seas fisheries - Yuan, Wei; Han, Shuli (Frontiers in Marine Science, 2025)
The principle of high seas fishing freedom, while historically significant, has increasingly revealed systemic shortcomings amid accelerating globalization and technological advances in fisheries. Over centuries, high seas fisheries governance has evolved from unregulated exploitation to managed operations, yet substantial challenges persist in achieving sound governance. Key issues include deficiencies in legal frameworks, insufficient international cooperation, inadequate regional fisheries management, and rampant IUU fishing. Guided by the Sustainable Development Goals and the UN Ocean Decade, this study proposes a governance transformation pathway through legislative and practical approaches, advocating strengthened legal frameworks and enhanced international cooperation across multiple levels to facilitate the transition from unrestricted fishing freedom to sustainable governance, engaging sovereign states, regional organizations and corporate entities in this process.